2020
DOI: 10.1021/acsmedchemlett.0c00272
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Covalent Inhibition of Plasmodium FK506 Binding Protein 35

Abstract: FK506-binding protein 35, FKBP35, has been implicated as an essential malarial enzyme. Rapamycin and FK506 exhibit antiplasmodium activity in cultured parasites. However, due to the highly conserved nature of the binding pockets of FKBPs and the immunosuppressive properties of these drugs, there is a need for compounds that selectively inhibit FKBP35 and lack the undesired side effects. In contrast to human FKBPs, FKBP35 contains a cysteine, C106, adjacent to the rapamycin binding pocket, providing an opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Generally, the IC 50 values for FKBP51 were higher, likely due to the higher tracer concentration, which was necessary due to the lower assay window. Comparison of the target engagement of Rapamycin towards the luciferase‐labelled FKBP12 with previously published results [8] showed that in spite of the different assay conditions (e. g., tracer affinity and concentration) the obtained IC 50 values (20 nM [8] and 8.5 nM, this work) were remarkably similar. In light of the results by Atack et al ., we conclude that the Rapamycin‐based tracer as well as our bicyclic [4.3.1] sulfonamide‐based tracers are useful.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Generally, the IC 50 values for FKBP51 were higher, likely due to the higher tracer concentration, which was necessary due to the lower assay window. Comparison of the target engagement of Rapamycin towards the luciferase‐labelled FKBP12 with previously published results [8] showed that in spite of the different assay conditions (e. g., tracer affinity and concentration) the obtained IC 50 values (20 nM [8] and 8.5 nM, this work) were remarkably similar. In light of the results by Atack et al ., we conclude that the Rapamycin‐based tracer as well as our bicyclic [4.3.1] sulfonamide‐based tracers are useful.…”
supporting
confidence: 77%
“…However, little is known to what extent these ligands occupy FKBPs or on the degree of occupancy needed to evoke biological effects. A recent study on irreversible ligands for FKBP35 of Plasmodium falciparum showed that intracellular activities of FKBP ligands may be substantially weaker than biochemical affinities and do not necessarily correlate with the latter [8] . Here, we report competitive NanoBRET assays [9] for human FKBP12, FKBP12.6, FKBP51 and FKBP52 for rapid profiling of target engagement of FKBP ligands in living cells.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, examples of enzyme-mediated site-specific protein labeling in vivo have been reported for endogenous mammalian proteins, such as O 6 -alkylguanine-DNA alkyltransferase (AGT) and dihydrofolate reductase (DHFR) [ 33 ]. These tags are used for background labeling of endogenous counterparts in mammalian cells and the non-covalent interactions that rely on labeling DHFR and FK506-binding protein (FKBP) in vivo, resulting in rapid dissociation and consequent signal degradation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of targets amenable to TCI approaches include aspartyl protease plasmepsin II, 11 Plasmodium proteasome, 9 glyceraldehyde 3-phosphate dehydrogenase, 12 and FKBP35. 13 There is no question that further targets that lend themselves to TCI approaches will be disclosed in the future.…”
mentioning
confidence: 99%